A filtering-based methodology for assessing evacuation performance in layout of complex infrastructures. Issue 5 (3rd September 2022) - Omidkhah Kharashtomi, Atefeh; Bemanian, Mohammadreza; Hafezi, Mohammadreza
Abstract : Evacuation is a performance matter in buildings design, and this study provides a framework for assessing the performance of complex architectural layouts for emergency egress. First, a theoretical framework is inspired by advanced estimation methods and extended to a performance model with spatial and computational sub-models. The spatial sub-model abstracts the floorplan as a geometric network. The computational sub-model is consisted of: filtering parameters, routing algorithm, and bottleneck importance calculation. A criterion called 'Bottleneck Importance (BI)' is introduced and formulated, which shows the effect of obstruction in each position in route on the evacuation performance of the floor. The model is applied in a case study, and outputs made it possible to analyse the performance of exits in-floor evacuation, frequent positions in the evacuation route, the topological relationship with performance, especially at intersections, and the effect of blocking in egress corridors and cause of obstructions.